Moral Standards in the Psychological Structure of the Personality of Students of Higher Education Institutions - Liakisheva, Anna; Salamakha, Ihor; Malimon, Liudmyla; Khanykina, Nataliia; Fedorenko, Maryna; Makieshyna, Yuliia (International Journal of Criminology and Sociology, 2021)
In this article’s scientific space, one can observe the differentiation of the definition of the terms "value", "value orientations" because it does not yet have a clear standard definition. Many researchers have dealt with this topic, researched, analyzed, observed, and made conclusions. However, there is still a rich scope for research of such phenomena of personal structure as value orientations. Outstanding psychologists-researchers who, in their scientific, practical, and theoretical works, dealt with the topic of values and value orientations and came to the general conclusion that values are a structural component of a personality, with the help of which a person achieves a goal, sets this goal, and characterizes position in life. The article saw the relationship between values and the basic structures of the personality, including value orientations—considered in values a system of orientation and personality attitudes.